PROCESSING OF DYNAMIC IMAGE SEQUENCES - BeknazarovaSaida Safibullayevna; Nuraliyev Nurbek; Salimov Mirzohid Muhammadjon o'g'li; Hasanov Jasurbek Ulug'bek o'g'li (International Engineering Journal For Research & Development, 2022)
The article describes an adaptation of the brightness control mechanism for processing dynamic image sequences, that in video codecs, the main compression of the video stream is provided by eliminating inter-frame redundancy using motion compensation methods for image fragments of adjacent frames. However, the use of motion compensation methods requires the formation of additional data (metadata) containing information about the types of image blocks used, the coordinates of their movement, etc. At the same time, in order to increase the compression of the video stream without compromising its quality, higher accuracy of motion compensation is required, which leads to an increase in the number of blocks and, accordingly, to an increase in the volume of metadata that reduces the effectiveness of motion compensation. This is the main problem of compressing streaming video without degrading the quality of images. In addition, the higher accuracy of positioning blocks with motion compensation dramatically reduces the speed of image processing, which is not always feasible in real-time systems. Therefore, MPEG-4-10 codecs use a rectangular block structure of variable size, which provides acceptable image quality at speeds of more than 3 Mbit/s.